Changes in paleostress and its magnitude related to seismic cycles in the Chelung‐pu Fault, Taiwan. Issue 12 (14th December 2015) - Hashimoto, Yoshitaka; Tobe, Kota; Yeh, En‐Chao; Lin, Weiren; Song, Sheng‐Rong
Abstract: Paleostress analysis was conducted through a multiple stress inversion method using slip data recoded for the core samples from the Taiwan Chelung‐pu Fault Drilling Project (TCDP). Two stress fields were obtained; one of these had horizontally plunging σ 1, and the other has horizontally plunging σ 2 or σ 3 in the compressional stress direction of the Chi‐Chi earthquake. Stress magnitude for both the stress fields was constrained by stress polygons, which indicated larger SHmax for horizontally plunging σ 1 than that in the case of horizontally plunging σ 2 or σ 3 . These differences in stress orientations and stress magnitude suggest that the change in stress filed can be caused by stress drop and stress buildup associated with seismic cycles. The seismic cycles recoded in the core samples from TCDP could include many events at geological timescale and not only the 1999 Chi‐Chi earthquake. Key Points: Switch in paleostress orientations was observed in Chelung‐pu Fault, Taiwan Larger stress magnitude was constrained for the stress with horizontally plunged compression Switch in paleostress can be caused by stress drop and building associated with seismic cycle